Post hoc analysis of a phase 3, multicenter, open‐label study of cenobamate for treatment of uncontrolled focal seizures: Effects of dose adjustments of concomitant antiseizure medications. (11th October 2021) - Rosenfeld, William E.; Abou‐Khalil, Bassel; Aboumatar, Sami; Bhatia, Perminder; Biton, Victor; Krauss, Gregory L.; Sperling, Michael R.; Vossler, David G.; Klein, Pavel; Wechsler, Robert
Abstract: Objective: To report post hoc results on how adjustments to baseline antiseizure medications (ASMs) in a subset of study sites (10 US sites) from a long‐term, open‐label phase 3 study of adjunctive cenobamate affected tolerability, efficacy, and retention. Methods: Patients with uncontrolled focal seizures taking stable doses of one to three ASMs were administered increasing doses of cenobamate (12.5, 25, 50, 100, 150, 200 mg/day) over 12 weeks at 2‐week intervals (target dose = 200 mg/day). Further increases to 400 mg/day by 50 mg/day biweekly increments were allowed during maintenance phase. Dose adjustments of cenobamate and concomitant ASMs were allowed. Data were assessed until last visit, at data cut‐off, on or after September 1, 2019. Results: A total of 240 patients meeting eligibility criteria were assessed (median [max] exposure 30.2 [43.0] months), with 177 patients continuing cenobamate at data cut‐off. Most common baseline concomitant ASMs were lacosamide, levetiracetam, lamotrigine, zonisamide, and clobazam. For most baseline concomitant ASMs, 70% of patients taking that ASM were continuing cenobamate at data cut‐off. Patients continuing cenobamate had greater mean ASM dose reductions and percent dose changes from baseline vs those who discontinued. Of patients continuing cenobamate, 24.6% discontinued one or more concomitant ASMs completely. Dose decreases for all concomitant ASMs generally occurred during titration or early maintenance phases and were mostly due to central nervous system (CNS)–related adverse events such as somnolence, dizziness, unsteady gait, and fatigue. Responder rates from ≥50% through 100% for patients continuing cenobamate were generally similar regardless of concomitant ASMs (of those most commonly taken), with 81% being ≥50% responders and 12% achieving 100% seizure reduction in the maintenance phase, which lasted up to 40.2 (median = 29.5) months. Significance: Concomitant ASM dose reductions were associated with more patients remaining on cenobamate. This is likely due to efficacy and improved tolerability, with overall reduced concomitant drug burden in patients with uncontrolled seizures despite taking one to three baseline concomitant ASMs.